The correlation between Lower Urinary Tract Symptoms and the quality of life of BPH patients at the Urology Clinic at RSD Mangusada Badung - Dewa Ayu Alit Widiasih (NHM PRESS, 2021)
Background:The severity of Lower Urinary Tract Symptoms (LUTS) in Benign Prostatic Hyperplasia (BPH) patients in the form of increased urinary frequency, nocturia, urinary incontinence, slow urine flow, interrupted urine flow, or dissatisfied sensation after urinating which will directly affect the quality of life. The decreased in the Quality of Life is caused by disturbance of their physical and physicological activity. Objective: This study purposed to determine the correlation between LUTS symptoms and the quality of life of BPH patients at the Urology Clinic of RSD Mangusada Badung. Method: This research used an analytic observational design with the cross sectional approach. Several samples were 52 respondents using the incidental sampling technique were then collected using the IPSS questionnaire and the WHOQOL-BREF questionnaire. Data were analyzed using Spearman`s rho test. Result: The results showed that most of the symptoms of LUTS were in the moderate category as many as 31 people with a percentage of 59.6% and the results of the measurement of most respondents that the quality of life was sufficient as many as 26 people with a percentage of 50%. Analysis of the correlation between LUTS symptoms and the quality of life of BPH patients obtained p-value <0.001. Conclusion: There is a correlation between LUTS symptoms and the quality of life of BPH patients at the Urology Clinic at RSD Mangusada Badung. The recommendations of this study are expected to be input for nurses to always implement education about LUTS symptoms and quality of life Keywords: LUTS, quality of life, BPH